Minimizing the influence of revolute joint clearance using the planar redundantly actuated mechanism. (August 2017) - Zhang, Xuchong; Zhang, Xianmin
Abstract: Joint clearance is unavoidable in real mechanism, so its effects should be minimized in order to fulfill the designed performances of the mechanism. In this paper, we proposed a method which is based on the redundantly actuated mechanism to minimize the influence of revolute joint clearance. A planar 3DOF redundantly actuated 4-R RR mechanism with 8 clearance joints is applied as an illustration to show how it works. Firstly, the kinematic and dynamic equations of the 4-R RR mechanism are established. Secondly, the joint clearance is geometrically described and the contact force models are introduced. After that, the joint clearances are restrained by preloading the passive links of the 4-R RR mechanism, the two-step Bathe integration method is used to solve these equations. Comparisons are made between the mechanisms with and without clearance restrain. Finally, experiments are carried out to verify the proposed method. Both simulation and experimental results show that the joint clearance can be successfully controlled by the redundantly actuated mechanism. Highlights: The performance of a redundant 4-R RR parallel mechanism with joint clearances is studied. A method is proposed to minimize the effects of clearance based on redundant mechanism. Both simulation and Experiment verified the effectiveness of the proposed methodology.